Literature Study: Risk Factors for the Incidence of Diabetes Mellitus in Productive Age in Indonesia - Dita Ayuningtiyas Tuti; Nur Lu’lu Fitriyani; Jaya Maulana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2024)
Diabetes mellitus (DM) is a type of degenerative disease that has increased continuously from year to year. as well as the occurrence of the biggest global health emergency in the 21st century. The increasing cases of diabetes mellitus every year have a negative impact on Indonesia, especially many diabetics are around productive age. productive age is the age with the highest rate of diabetes mellitus in Indonesia with the following age groups and prevalence: 15-24 years of age by 0.1%, age 25-34 by 0.2%, age 35-44 by 1.1%, and age 45-64 by 6.3%, thus it can be said that the increasing age is increasingly at risk of diabetes mellitus. The purpose of writing a literature review is to find out what risk factors affect the incidence of diabetes mellitus at productive age in Indonesia. The research design in the study uses the Literature Review method. Research journal articles using online database facilities through the Google Scholar page published in the period 2020-2023 (4 years). Based on the results of research from 10 articles, it was found that there was a relationship between family history, diet, sleep patterns, physical activity, obesity, and hypertension with the incidence of leprosy in Indonesia.